Deception improves time trial erformance in well-trained cyclists without augmented fatigue - Ansdell, P.; Thomas, K.; Howatson, G.; Amann, M.; Goodall, S. (Medicine & Science in Sports & Exercise, 2018)
PURPOSE: To investigate the effects of feedback, in the form of a virtual avatar paced at 100% and 102% of baseline performance, on neuromuscular fatigue after a 4-km cycling time trial (TT). We hypothesized that improved cycling performance would occur because of the participants exceeding a previously established critical threshold and experiencing greater neuromuscular fatigue.